INFLUENCE OF FLIGHT CONFIGURATION USED FOR LiDAR DATA COLLECTION ON INDIVIDUAL TREES DATA EXTRACTION IN FOREST PLANTATIONS - Muller, Mauricio; Kersting, Ana Paula Baungarten; Nakajima, Nelson Yoshihiro; Hosokawa, Roberto Tuyoshi; Rosot, Nelson Carlos (Floresta, 2014)
Abstract In the last decades, several studies have been conducted aiming to the extraction of forest variables from LiDAR data. Although such studies have indicated great potential, the high cost associated with LiDAR data acquisition process inhibits the technology to become an operational technique for forestry applications. The cost of a LiDAR survey, as for any other data collection techniques, is composed of fixed and variable costs. The variable portion, which can be optimized, is dependent, among other factors, on the number of flight hours. The flight time is mainly dependent on the flight configuration used for the survey. The objective of this paper is to investigate the impact of using different operational parameters on different species of forest plantations, to provide inputs for an adequate cost-benefit analysis. The different configurations are evaluated in terms of the number of individual trees automatically detected, individual height and volume, using the forest inventory as the reference data. The experiments have shown that compatible results are obtained using different configurations with flight time varying by a factor of 3.5 to 10 times. Also, for a given point density, preference should be given to the configuration based on a lower flying height. Keywords: Airborne LiDAR; remote sensing; progressive densification; forest mensuration; operational parameters; tree height; volume. Resumo Influência da configuração de voo para aquisição de dados LiDAR na extração de dados de árvores individuais em plantios florestais. Nas últimas décadas, vários estudos têm sido realizados visando à utilização dos dados obtidos através da tecnologia LiDAR (Light Detection And Ranging) na obtenção de variáveis florestais. Embora tais estudos indiquem alto potencial do LiDAR para aplicações florestais, o elevado custo do levantamento dificulta sua operacionalização no meio florestal. O custo de um levantamento LiDAR, como em outros tipos de levantamentos, é composto de custos fixos e variáveis. A parcela de custos variáveis, a qual pode ser otimizada, encontra-se associada, dentre outros fatores, ao número de horas de voo. O tempo de voo depende principalmente da configuração de voo utilizada no levantamento. Este artigo visa analisar a influência da utilização de diferentes parâmetros operacionais para diferentes espécies de plantios florestais, objetivando prover insumos para uma adequada análise custo-benefício. As configurações são avaliadas em termos do número de árvores automaticamente identificadas, altura individual e volume, tendo como referência os dados do inventário florestal. Os experimentos realizados demonstraram que resultados comparáveis são obtidos com a utilização de diferentes configurações com tempo de voo variando de um fator de 3,5 a 10 vezes. Observou-se também que para uma dada densidade de pontos deve-se dar preferência à configuração que utilize menor altura de voo. Palavras-chave: Laser scanner; sensoriamento remoto; parâmetros operacionais; altura; volume.